Peran Tunjangan pada Produktivitas Pekerja UMKM di Tangerang Selatan (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
Employee productivity serves as a crucial factor for MSMEs sustainability amid competitive labor market conditions. This study aims to analyze the role of employee benefits on worker productivity in MSMEs across South Tangerang using a qualitative approach through in-depth interviews with 24 informants consisting of 12 MSME owners and 12 employees in culinary, fashion, and service sectors. Research findings indicate that mandatory benefits such as BPJS Health reduce sick leave absences by up to 51%, while discretionary benefits in the form of performance bonuses increase production output by up to 30%. Benefits influence productivity through two pathways: fulfilling basic needs that enable optimal work focus and mediating job satisfaction that enhances intrinsic motivation. Business sectors determine benefit type priorities, where culinary emphasizes meal allowances while fashion prioritizes production bonuses. MSMEs with consistent and structured benefit sistems achieve significant productivity improvements despite facing financial constraints. The optimal strategy involves phased implementation focusing on benefits that deliver the greatest impact on specific job characteristics. This research recommends human resource management assistance for MSME practitioners to design effective and sustainable compensation sistems.